Anion exchange membrane and preparation method thereof
By using anion exchange polymer composed of porous polymer support and crosslinked monomer in the anion exchange membrane, the problem of insufficient chemical resistance of the existing membrane under high concentrations of acid and alkali is solved, and the film performance with low sheet resistance and high ion exchange capacity is achieved.
Patent Information
- Application Number
- CN202380054710.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-18
- Filing Date
- 2023-05-25
- Publication Date
- 2025-04-11
AI Technical Summary
The existing anion exchange membranes are insufficient chemical resistance under high concentrations of acid and alkali, and it is difficult to achieve low sheet resistance and high ion exchange capacity at the same time.
An anion exchange membrane consisting of a porous polymer support and an anion exchange polymer containing a specific crosslinking monomer is used to form uniformly distributed anion exchange groups on the surface of the membrane and inside the pores by a photoinitiator crosslinking reaction.
It achieves excellent chemical resistance under high concentrations of acid and alkali, has low sheet resistance and high ion exchange capacity, and is suitable for water treatment systems such as electrodialysis and bipolar membrane electrodialysis.
Smart Images

Figure CN119816548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anion exchange membrane and a preparation method thereof. Background Art
[0002] Ion exchange membrane refers to a synthetic resin membrane that selects cations and anions to allow only one of the ions to penetrate. Among them, anion exchange membrane is a synthetic resin membrane that has a positively charged functional group to allow anions to selectively penetrate. This anion exchange membrane can be applied to water treatment systems such as electrodialysis, bipolar membrane electrodialysis, storage desalination, and electrodeionization, or to fuel cells, water electrolysis, reverse electrodialysis, redox flow batteries, and other systems. The system using anion exchange membrane can apply acidic or alkaline raw water to the process, and acid or alkali may be produced during the process operation of raw water. Here, as anion exchange membrane, perfluoro anion exchange membrane can be used, but due to its high price, hydrocarbon-based anion exchange membrane is applied in actual systems. However, hydrocarbon-based anion exchange membranes are limited in application process and conditions due to chemical resistance problems. In addition, since the anion exchange membrane has a certain support body fraction in its membrane, it is limited in increasing the ion exchange capacity to improve the membrane properties. Summary of the invention Technical issues
[0003] One aspect provides an anion exchange membrane having low sheet resistance and high ion exchange capacity and having excellent chemical resistance in the presence of high concentrations of acid and base.
[0004] On the other hand, a method for preparing the anion exchange membrane is provided. Technical Solution
[0005] According to one aspect, an anion exchange membrane is provided, comprising:
[0006] A porous polymer support made of a membrane structure; and
[0007] Anion exchange polymer, wherein
[0008] The anion exchange polymer is located on the surface and inside the pores of the porous polymer support.
[0009] The anion exchange groups of the anion exchange polymer are evenly distributed on the surface and inside the pores of the porous polymer support.
[0010] And the anion exchange polymer is a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following Chemical Formula 1:
[0011] [Chemical formula 1]
[0012]
[0013] In the formula,
[0014] X - F - , Cl - Br - or I - .
[0015] The membrane structure may be a structure with regularly arranged pores or a three-dimensional network structure.
[0016] The porosity of the membrane structure may be 30% to 80%.
[0017] The film structure may include polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, One or more polymers selected from the group consisting of polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone.
[0018] The porous polymer support may have a thickness of 10 μm to 110 μm.
[0019] The anion exchange membrane may have an average thickness of 10 μm to 200 μm.
[0020] The anion exchange membrane may have an ion exchange capacity equal to or greater than 1.5 meq / g.
[0021] The sheet resistance of the anion exchange membrane may be equal to or less than 10Ω·cm 2 .
[0022] The anion exchange membrane can be used for electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, and water electrolysis system.
[0023] According to another aspect, a method for preparing an anion exchange membrane is provided, comprising the following steps:
[0024] Providing a porous polymer support made of a membrane structure;
[0025] preparing a composition for forming an anion exchange polymer, wherein the composition for forming an anion exchange polymer comprises a crosslinking monomer represented by the following Chemical Formula 1, a photoinitiator, and a solvent;
[0026] impregnating the porous polymer support with the anion exchange polymer-forming composition to fill the surface and pores of the porous polymer support with the composition;
[0027] Pressing a polyester base film on at least one surface of a porous polymer support filled with the composition to prepare a laminate having the polyester base film and the porous polymer support laminated thereon;
[0028] irradiating the laminate with light and causing the composition to undergo a cross-linking reaction to form an anion exchange polymer as a cross-linked product of the composition on the surface of the porous polymer support and inside the pores; and
[0029] The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane:
[0030] [Chemical formula 1]
[0031]
[0032] In the formula,
[0033] X - F - , Cl - Br - or I - .
[0034] The crosslinking monomer represented by the Chemical Formula 1 may be included in an amount of 30 wt % to 70 wt % based on 100 wt % in total of the anion exchange polymer-forming composition.
[0035] Before impregnating the porous polymer support with the anion exchange polymer-forming composition, The method may further include immersing the porous polymer support in a surfactant solution and drying the solution to prepare a porous polymer support having a hydrophilized surface.
[0036] The light irradiation uses UVC as ultraviolet light at 2000 mJ / cm 2 Up to 10000mJ / cm 2 irradiate with the amount of light. Beneficial Effects
[0037] According to one aspect, an anion exchange membrane is a membrane in which an anion exchange polymer, which is a cross-linked bonding product of a composition comprising a cross-linking monomer represented by the above Chemical Formula 1, is located on the surface and inside the pores of a porous polymer support made of a membrane structure, and anion exchange groups of the anion exchange polymer are uniformly distributed on the surface and inside the pores of the porous polymer support.
[0038] The anion exchange membrane can have high ion exchange capacity and low sheet resistance by increasing the content of anion exchange polymer in the anion exchange membrane. In addition, since the anion exchange membrane has excellent chemical resistance, it can be used under high concentration acid and alkali conditions. Brief description of the attached figure
[0039] Figure 1 A conceptual diagram of a general anion exchange membrane.
[0040] Figure 2 FIG. 1 is a schematic diagram of an anion exchange membrane according to one embodiment.
[0041] Figure 3 This is a scanning electron microscope (SEM) photograph of the structure of the porous polymer support used in the anion exchange membrane prepared in Example 1.
[0042] Figure 4 The schematic flow chart of a method for preparing an anion exchange membrane according to one embodiment is shown. DETAILED DESCRIPTION
[0043] Hereinafter, an anion exchange membrane and a method for preparing the same will be described in detail with reference to embodiments of the present invention and the accompanying drawings. These embodiments are merely illustrative to describe the present invention in more detail, and it is apparent to those skilled in the art that the scope of the present invention is not limited to these embodiments.
[0044] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those generally understood by technicians in the technical field to which the present invention belongs. In case of conflict, the present specification including the definition shall prevail. Although methods and materials similar or identical to those described in this specification can be used for the implementation or testing of the present invention, the present invention describes suitable methods and materials. In this specification, the term "comprising" means that other constituent elements can be further included, rather than excluding other constituent elements, unless otherwise described to the contrary. In this specification, the term "these combinations" refers to a mixture or combination with one or more described constituent elements. In this specification, the term "and / or" includes any combination and all combinations of one or more items related to each other. In this specification, the term "or" refers to "and / or". In this specification, "at least one" or "one or more" in front of a constituent element can supplement the list of all constituent elements, and does not mean that the individual constituent elements described above can be supplemented. In this specification, when a constituent element is arranged "on" or "above" another constituent element, a constituent element can be directly arranged on another constituent element, or other constituent elements can be between the constituent elements. On the other hand, when a component is disposed "directly" on or "over" another component, there may be no intervening components. In this specification, "~-based resin", "~-based polymer", "BPA-based polymer" and / or "BPA-based copolymer" is a broad concept, which includes "BPA resin", "BPA polymer", "BPA polymer", "BPA copolymer" and / or "derivatives of BPA resin, polymer, polymer or copolymer". In this specification, the term "polymer or copolymer cross-linked by these resins" means "polymer or copolymer cross-linked by the aforementioned resin".
[0045] Figure 1 A conceptual diagram of a general anion exchange membrane.
[0046] See also Figure 1 In the anion exchange membrane 10, an anion exchange polymer main chain 2 having a cationic functional group 1 is arranged on a support 5. When the counter anion 3 and the common cation 4 penetrate from the left to the right, the anion exchange membrane 10 selectively penetrates the counter anion 3.
[0047] In general, anion exchange membrane 10 requires high penetration selectivity, low resistance, excellent mechanical strength and high chemical stability etc. The material used for anion exchange membrane 10 comprises perfluorinated anion exchange membrane and hydrocarbon anion exchange membrane. Wherein, hydrocarbon anion exchange membrane has excellent price competitiveness, but because chemical resistance is weaker, it is limited in application process and conditions. In addition, because hydrocarbon anion exchange membrane has a certain support body fraction, it is limited in increasing ion exchange capacity to improve membrane performance.
[0048] In view of this, the inventors of the present invention will propose the following anion exchange membrane and method for preparing the same.
[0049] The anion exchange membrane according to one embodiment comprises: a porous polymer support made of a membrane structure; and an anion exchange polymer, wherein the anion exchange polymer is located on the surface and inside the pores of the porous polymer support, and the anion exchange groups of the anion exchange polymer are uniformly distributed on the surface and inside the pores of the porous polymer support, and the anion exchange polymer can be a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following Chemical Formula 1:
[0050] [Chemical formula 1]
[0051]
[0052] In the formula,
[0053] X - F - , Cl - Br - or I - .
[0054] The anion exchange membrane according to one embodiment can have high ion exchange capacity and low sheet resistance by increasing the content of anion exchange polymer in the anion exchange membrane. In addition, since the anion exchange membrane has excellent chemical resistance, it can be used under high concentration acid and alkali conditions.
[0055] Figure 2 FIG. 1 is a schematic diagram of an anion exchange membrane according to one embodiment.
[0056] See also Figure 2In the anion exchange membrane 40 according to an embodiment, the anion exchange polymer 31 having a cationic functional group is located on the surface of the porous polymer support 20 and inside the pores 21. Since the anion exchange polymer 31 having a cationic functional group is uniformly distributed on the surface of the porous polymer support 20 and inside the pores 21, a homogeneous anion exchange membrane 40 can be obtained. The structure of this anion exchange membrane 40 can have low sheet resistance and high ionic conductivity. In addition, the porous polymer support 20 can improve mechanical durability and has high dimensional stability.
[0057] The anion exchange polymer can be a cross-linked product of a composition comprising a cross-linking monomer represented by the chemical formula 1. The cross-linking monomer represented by the chemical formula 1 is a monomer cross-linked by two vinylbenzyl chlorides and a bi-functional cyclic diamine, wherein the bi-functional cyclic diamine comprises pendant chains with quaternary ammonium cation groups. The cross-linking monomer represented by the chemical formula 1 forms a rigid cage structure, thereby maintaining chemical stability even under high concentration acid or alkali conditions while improving ion exchange capacity. Therefore, an anion exchange membrane comprising such an anion exchange polymer can have excellent concentration and desalination performance. "Cross-linked product" refers to, in addition to the cured product of the composition comprising the cross-linking monomer represented by the chemical formula 1, all initial reaction products, intermediate reaction products and final products are also included.
[0058] The membrane structure may be a structure with regularly arranged pores or a three-dimensional network structure. Figure 3 The structure of such a membrane structure is confirmed in the method. For example, the membrane structure is prepared by mixing a polymer material and a low molecular weight wax and extruding them into a film at a high temperature, and then forming a microporous structure by extracting the wax with a solvent, or the pore structure can be formed by a uniaxial or biaxial stretching and heat treatment process without using wax. However, it is not limited thereto, and the membrane structure can be formed by all preparation methods available in the art.
[0059] The porosity of the membrane structure can be 30% to 80%. For example, the porosity of the membrane structure can be 35% to 70%, or can be 40% to 65%, or can be 45% to 60%, or can be 45% to 55%. If the pore size or / and porosity of the membrane structure is less than 30%, it is difficult to improve the physical durability and mechanical strength of the anion exchange membrane required as a porous polymer support. If the pore size or / and porosity of the membrane structure exceeds 80%, the fraction of the porous polymer support in the anion exchange membrane may be too much, resulting in an increase in sheet resistance and a decrease in ion exchange capacity.
[0060] The film structure may include polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, One or more polymers selected from the group consisting of polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone. For example, the membrane structure may be polyethylene or polypropylene. For example, the membrane structure may be polypropylene.
[0061] The thickness of the porous polymer support may be 10 μm to 110 μm. For example, the thickness of the porous polymer support may be 20 μm to 110 μm, or may be 40 μm to 110 μm, or may be 60 μm to 110 μm. Within the thickness range of the porous polymer support, sheet resistance may be reduced and ion exchange capacity may be increased.
[0062] The average thickness of the anion exchange membrane may be 10 μm to 200 μm. For example, the average thickness of the anion exchange membrane may be 12 μm to 150 μm. If the average thickness of the anion exchange membrane is less than 10 μm, the physical durability and operability of the anion exchange membrane are reduced, resulting in a risk of membrane damage during operation when the module is tightened or applied to the system, and the system operating performance may be reduced due to the penetration of unnecessary ions. If the average thickness of the anion exchange membrane exceeds 200 μm, the sheet resistance increases, resulting in an increase in the power consumption required when applied to the system, etc., and the system operating performance may be reduced.
[0063] The ion exchange capacity of the anion exchange membrane may be equal to or greater than 1.5 meq / g. For example, the ion exchange capacity of the anion exchange membrane may be equal to or greater than 1.6 meq / g, or may be equal to or greater than 1.7 meq / g, or may be equal to or greater than 1.8 meq / g, or may be equal to or greater than 1.9 meq / g, or may be equal to or greater than 2.0 meq / g, or may be equal to or greater than 2.1 meq / g, or may be equal to or greater than 2.2 meq / g, or may be equal to or greater than 2.3 meq / g, or may be equal to or greater than 2.4 meq / g.
[0064] The sheet resistance of the anion exchange membrane may be equal to or less than 10Ω·cm 2 For example, the sheet resistance of the anion exchange membrane may be equal to or less than 9.9 Ω·cm. 2 , or can be equal to or less than 9.8Ω·㎝ 2 , or can be equal to or less than 9.7Ω·㎝ 2 , or can be equal to or less than 9.6Ω·cm 2, or can be equal to or less than 9.0Ω·cm 2 , or can be equal to or less than 8.5Ω·cm 2 , or can be equal to or less than 8.0Ω·㎝ 2 , or can be equal to or less than 7.8Ω·cm 2 , or can be equal to or less than 7.6 Ω·cm 2 , or can be equal to or less than 7.2Ω·㎝ 2 , or can be equal to or less than 6.5Ω·cm 2 , or can be equal to or less than 6.0Ω·cm 2 , or can be equal to or less than 5.0Ω·cm 2 , or can be equal to or less than 4.0Ω·㎝ 2 , or can be equal to or less than 3.0Ω·㎝ 2 .
[0065] The anion exchange membrane can be used for electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, and water electrolysis system. The anion exchange membrane may have excellent concentration and desalination performance.
[0066] According to another embodiment, a method for preparing an anion exchange membrane may include the following steps: providing a porous polymer support made of a membrane structure; preparing a composition for forming an anion exchange polymer, wherein the composition for forming an anion exchange polymer comprises a cross-linking monomer represented by the following chemical formula 1, a photoinitiator, and a solvent; impregnating the porous polymer support with the composition for forming anion exchange polymer to fill the composition on the surface and inside the pores of the porous polymer support; pressing a polyester base film on at least one surface of the porous polymer support filled with the composition to prepare a laminated body laminated with the polyester base film and the porous polymer support; irradiating light to the laminated body and causing the composition to cross-link to react to form an anion exchange polymer as a cross-linked bonding product of the composition on the surface and inside the pores of the porous polymer support; and peeling off the polyester base film from the porous polymer support on which the anion exchange polymer is formed on the surface and inside the pores to prepare an anion exchange membrane:
[0067] [Chemical formula 1]
[0068]
[0069] In the formula,
[0070] X - F - , Cl - Br - or I - .
[0071] The method for preparing an anion exchange membrane can provide an anion exchange membrane having low sheet resistance and high ion exchange capacity and having excellent chemical resistance in the presence of high concentrations of acid and base.
[0072] Figure 4 The schematic flow chart of a method for preparing an anion exchange membrane according to one embodiment is shown.
[0073] See also Figure 4 First, a porous polymer support made of a membrane structure is provided (step S1).
[0074] The porosity of the membrane structure can be 30% to 80%. For example, the porosity of the membrane structure can be 35% to 70%, or can be 40% to 65%, or can be 45% to 60%, or can be 45% to 55%. If the pore size or / and porosity of the membrane structure is less than 30%, it is difficult to improve the physical durability and mechanical strength of the anion exchange membrane required as a porous polymer support. If the pore size or / and porosity of the membrane structure exceeds 80%, the fraction of the porous polymer support in the anion exchange membrane may be too much, resulting in an increase in sheet resistance and a decrease in ion exchange capacity.
[0075] The membrane structure may include one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylethersulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone. For example, the membrane structure may be polyethylene or polypropylene. For example, the membrane structure may be polypropylene.
[0076] The thickness of the porous polymer support may be 10 μm to 110 μm. For example, the thickness of the porous polymer support may be 20 μm to 110 μm, or may be 40 μm to 110 μm, or may be 60 μm to 110 μm. Within the thickness range of the porous polymer support, sheet resistance may be reduced and ion exchange capacity may be increased.
[0077] Since the membrane structure has hydrophobicity, sufficient wettability with the anion exchange polymer may not be ensured, and as a result, desired membrane performance may not be achieved.
[0078] In order to improve this point, before the porous polymer support is impregnated with the anion exchange polymer forming composition, the porous polymer support may be further immersed in a surfactant solution and dried to prepare a porous polymer support having a hydrophilic surface. As long as it can be hydrophilized in the art, the surfactant can be used without restriction, for example, one or more materials selected from dodecylbenzenesulfonic acid (DBSA), alkylbenzenesulfonic acid (ABS), linear alkylbenzenesulfonic acid (LAS), alpha-sulfonic acid (AS), alpha-olefin sulfonic acid (AOS), alcohol polyoxyethylene ether (AE) and alcohol polyoxyethylene ether sulfonic acid (AES) can be used. For example, the surfactant can be dodecylbenzenesulfonic acid. When the hydrophobic part of the surfactant is attached to the surface of the hydrophobic porous polymer support by hydrophobic-hydrophobic interaction (hydrophobic-hydrophobic interaction), the hydrophilic part of the surfactant covers the surface of the porous polymer support and replaces the hydrophobicity on the surface, so as to achieve hydrophilization. At this time, the surfactant can not only make the outer surface hydrophilization of the porous polymer support, but also the surface hydrophilization of the entire internal pores. However, if the hydrophilization degree of the porous polymer support is enough, or if the pores of the porous polymer support are large enough, so as to be able to fill the anion exchange polymer to form a composition, it can be omitted.
[0079] The surfactant solution may include 0.001 wt % to 6 wt % of a surfactant and the remainder being a solvent. For example, the surfactant solution may include 0.01 wt % to 4 wt % of a surfactant and the remainder being a solvent, or may include 0.05 wt % to 3 wt % of a surfactant and the remainder being a solvent. If the content of the surfactant contained in the surfactant solution is less than 0.001 wt %, the surface of the porous polymer support is not hydrophilized, resulting in that the anion exchange polymer-forming composition may be If the content of the surfactant contained in the surfactant solution exceeds 6% by weight, the surfactant may be eluted or the filling amount of the anion exchange polymer-forming composition may be reduced.
[0080] The immersion may be performed for 0.1 to 10 minutes, for example, 0.5 to 5 minutes. If the immersion time is shorter than 0.1 minutes, the surface of the porous polymer support is not sufficiently hydrophilized, resulting in the anion exchange polymer-forming composition being unable to fill the pores of the porous polymer support. 10 minutes, the production speed may be reduced and the production cost may be increased. The drying may be performed at a temperature of 40°C to 90°C for 1 minute to 20 minutes. For example, the drying may be performed at a temperature of 40°C to 80°C for 1 minute to 10 minutes.
[0081] Next, a composition for forming an anion exchange polymer is prepared, wherein the composition for forming an anion exchange polymer includes a crosslinking monomer represented by the following Chemical Formula 1, a photoinitiator, and a solvent (step S2).
[0082] The crosslinking monomer represented by the chemical formula 1 is a monomer of two vinylbenzyl chlorides and a bifunctional cyclic diamine (bi- The cross-linked monomer represented by the chemical formula 1 forms a rigid cage structure, thereby maintaining chemical stability even under high concentration acid or alkali conditions while improving ion exchange capacity. Therefore, an anion exchange membrane comprising such an anion exchange polymer can have excellent concentration and desalination performance. "Cross-linked combined product" refers to a product comprising all initial reaction products, Intermediate Reaction Product and Final Product The crosslinking monomer represented by the Chemical Formula 1 may be included in an amount of 30 wt % to 70 wt % based on 100 wt % in total of the anion exchange polymer-forming composition.
[0083] The photoinitiator may be 0.01 based on 100 wt % of the total anion exchange polymer-forming composition. % to 2% by weight, or may be 0.1% to 1% by weight. As long as the photocatalyst available in the art The photoinitiator can be used without limitation, for example, 2-hydroxy-2-methylpropiophenone As long as the solvent is available in the art, the solvent can be used without limitation, for example, it can be a water-soluble solvent such as water, methanol or ethanol, or it can be a distilled water solvent such as distilled water. The solvent may be removed from the anion exchange polymer-forming composition by the chemical formula 1 The remaining amount of the crosslinking monomer and the photoinitiator is included.
[0084] Next, the porous polymer support is impregnated with the anion exchange polymer-forming composition. The composition is filled in the surface and pores of the porous polymer support (S3 step). The impregnation can be carried out for 0.1 minute to 10 minutes, for example, 0.5 minute to 5 minutes. If the impregnation time is less than 0.1 minute, the anion exchange polymer forming composition will not be fully filled in the pores of the porous polymer support, causing the performance of the anion exchange membrane to decline, or leakage (leak) may occur. If the impregnation time exceeds 10 minutes, the production speed may decrease, and the production cost may increase. Through the impregnation, the anion exchange polymer forming composition can be filled in the pores of the porous polymer support, and the anion exchange polymer forming composition can cover the outer surface of the porous polymer support.
[0085] Next, a polyester base film is pressed onto at least one surface of the porous polymer support filled with the composition to prepare a laminated body in which the polyester base film and the porous polymer support are laminated (step S4).
[0086] The polyester base film can be pressed on the upper surface or / and lower surface of the porous polymer support by roller calendering. The polyester base film can be a polyethylene terephthalate film. The thickness of the polyester base film can be 10 μm to 150 μm, for example, 20 μm to 120 μm, or 30 μm to 100 μm. If the thickness of the polyester base film is less than 10 μm, when laminated with a support filled with an anion exchange polymer, lamination defects such as wrinkles on the film may occur. If the thickness of the polyester base film exceeds 150 μm, the thickness of the polyester base film is too large during the cross-linking reaction described later, and the light may not be fully irradiated to the porous polymer support, resulting in the possibility that the cross-linking reaction may not occur fully. A surface of the polyester base film in contact with the porous polymer support may be untreated, or may be subjected to demolding treatment. By using this film, the combination with the porous polymer support having a hydrophilic surface is hindered, thereby preventing the anion exchange polymer from falling off the surface of the support. The pressing may be performed at a temperature of 10°C to 35°C, such as 15°C to 30°C, and a pressure of about 0 bar to 5 bar. The pressure can be appropriately adjusted in consideration of the thickness of the porous polymer support and the thickness of the polyester base film.
[0087] Next, the laminate is irradiated with light to cause a cross-linking reaction of the composition, thereby forming an anion exchange polymer as a cross-linked product of the composition on the surface of the porous polymer support and inside the pores (step S5).
[0088] The light may be ultraviolet light, for example, UVA, UVB, UVC or / and UVV. For example, the light irradiation may use UVC as ultraviolet light at 2000 mJ / cm. 2 Up to 10000mJ / cm 2 For example, at 2000 mJ / cm 2 Up to 8000mJ / cm 2 If the amount of ultraviolet light irradiated and the irradiation time are less than the above range, the cross-linking reaction of the anion exchange polymer forming composition may not proceed smoothly. If the amount of ultraviolet light irradiated and the irradiation time exceed the above range, the porous polymer support and the polyester base film may be melted or carbonized due to excessive energy.
[0089] Finally, the polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane (step S6). The peeling can be completed by pulling the polyester base film on the porous polymer support in opposite directions using a peeling roller.
[0091] Hereinafter, the present invention will be described in more detail by way of examples. However, the examples are only used to describe the present invention in more detail, and the scope of the present invention is not limited to these examples.
[0093] [Example]
[0095] Example 1: Preparation of anion exchange membrane
[0096] A polypropylene porous polymer support having a thickness of 60 μm (porosity: 55%) was prepared.
[0097] In addition, a 4-vinylbenzyl chloride solution dissolved in methanol was added to a 1,4-diazabicyclo[2,2,2]octane solution dissolved in methanol so that the molar ratio of vinylbenzyl chloride to 1,4-diazabicyclo[2,2,2]octane was 2:1, and stirred under an inert atmosphere at room temperature to prepare a mixture. The mixture was filtered, washed with methanol, and then vacuum dried at room temperature to obtain a crosslinking monomer represented by the following Chemical Formula 1.
[0098] 66 wt % of the crosslinking monomer represented by the Chemical Formula 1, 0.6 wt % of a 2-hydroxy-2-methylpropiophenone (manufactured by Ciba) photoinitiator, and the remaining amount of distilled water were mixed to prepare a total of 100 wt % of an anion exchange polymer-forming composition.
[0099] The polypropylene porous polymer support is impregnated with the anion exchange polymer forming composition to fill the composition on the surface and inside the pores of the porous polymer support. The porous polymer support filled with the composition is put into a pressing roller, and a polyester film with a thickness of 50 μm is pressed on the upper and lower surfaces of the porous polymer support at room temperature to prepare a laminated body laminated with the polyester film and the porous polymer support. UVC is used as ultraviolet light at 3000 mJ / cm 2 The laminate is irradiated with a light amount of 100 to form an anion exchange polymer as a cross-linked product of the composition on the surface and inside the pores of the porous polymer support. The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane.
[0100] [Chemical formula 1]
[0101]
[0102] In the formula, X - Cl - .
[0104] Example 2: Preparation of anion exchange membrane
[0105] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polypropylene porous polymer support having a thickness of 80 μm (porosity: 45%) was used.
[0107] Example 3: Preparation of anion exchange membrane
[0108] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polypropylene porous polymer support having a thickness of 110 μm (porosity: 48%) was used.
[0110] Comparative Example 1: Preparation of anion exchange membrane
[0111] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polypropylene porous polymer support having a thickness of 120 μm (porosity: 28%) was used.
[0113] Comparative Example 2: Preparation of anion exchange membrane
[0114] An anion exchange membrane was prepared in the same manner as in Example 1 except that a cellulose acetate nonwoven fabric type support (porosity: 75%) having a thickness of 60 μm was used.
[0116] Comparative Example 3: Preparation of anion exchange membrane
[0117] An anion exchange membrane was prepared in the same manner as in Example 1, except that a polyethylene / polypropylene mesh type support having a thickness of 20 μm (porosity: 84%) was used.
[0119] Comparative Example 4: Preparation of anion exchange membrane
[0120] An anion exchange membrane was prepared in the same manner as in Example 1 except that a polyethylene porous polymer support having a thickness of 8 μm (porosity: 44%) was used.
[0122] Comparative Example 5: Preparation of anion exchange membrane
[0123] An anion exchange membrane was prepared in the same manner as in Example 1, except that 42 wt % of (3-acrylamidopropyl)trimethylammonium chloride (manufactured by TCI), 14 wt % of N,N'-methylenebisacrylamide (manufactured by Merck), 0.6 wt % of 2-hydroxy-2-methylpropiophenone (manufactured by Ciba) as a photoinitiator, and the remaining amount of distilled water were mixed to use a total of 100 wt % of the anion exchange polymer-forming composition.
[0125] Analysis Example 1: Scanning Electron Microscope (SEM) Photograph
[0126] The structure of the porous polymer support of the anion exchange membrane prepared in Example 1 was observed using a scanning electron microscope (SEM) at a magnification of x30K. As a scanning electron microscope, Hitachi's S-5500 was used. The results are shown in FIG. Figure 3 shown.
[0127] See also Figure 3 It can be confirmed that the porous polymer support of the anion exchange membrane prepared in Example 1 has a three-dimensional network structure.
[0129] Evaluation Example 1: Physical Property Evaluation
[0130] As described below, the physical properties of each of the anion exchange membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were evaluated. The results are shown in Table 1 below.
[0131] (1) Sheet resistance (Ω·cm) 2 )
[0132] The samples were prepared by cutting each anion exchange membrane into a size of 5 cm × 5 cm. The samples were immersed in a 0.5 M NaCl aqueous solution for 24 hours. The samples were placed between the electrodes for sheet resistance measurement, and the wire resistance R1 of the anion exchange membrane and the resistance R2 of the 0.5 M NaCl aqueous solution were measured by using an LCR meter (E4908A, Agilent). The measured resistance values R1 and R2 were substituted into the following formula 1 to obtain the sheet resistance Rm. The results are shown in Table 1.
[0133] [Formula 1]
[0134] Rm(Ω·cm 2 )=(R1-R2)x S
[0135] In the formula,
[0136] Rm is the sheet resistance of the anion exchange membrane,
[0137] R1 is the wire resistance of the anion exchange membrane,
[0138] R2 is the resistance of 0.5M NaCl aqueous solution,
[0139] S is the area of the electrode.
[0141] (2) Ion Exchange Capacity (IEC, meq / g)
[0142] Prepare the sample by cutting each anion exchange membrane into a size of 5 cm × 5 cm. Wash the sample with distilled water and then use a paper towel to remove extra moisture. Fill 70 ml of 1M NaCl solution in a vial, then place the sample to remove moisture in a 1M NaCl solution, immerse for 12 hours or more, and perform a pretreatment. Then, wash the sample that has completed a pretreatment several times with distilled water, and use a paper towel to remove extra moisture. Fill 70 ml of 0.5M Na2CO3 solution in a vial, then place the sample to remove moisture in a 0.5M Na2CO3 solution, immerse for 12 hours or more, and perform a secondary pretreatment. Then, remove the sample that has completed the secondary pretreatment from the vial, and titrate the remaining solution with 0.01M AgNO3 solution, and record the volume of the AgNO3 solution put in the titration process. Wash the sample several times with distilled water, then dry it in a hot air oven at 80°C for 15 minutes. After drying, measure the weight of the dried anion exchange membrane. The measured weight of the dried anion exchange membrane was substituted into the following formula 2 to obtain the ion exchange capacity (IEC). The results are shown in Table 1.
[0143] [Formula 2]
[0144] IEC (meq / g) = (volume of titration reagent (ml) × 0.01) / weight of dried anion exchange membrane (g)
[0146] (3) Chemical resistance
[0147] The samples were prepared by cutting the anion exchange membranes prepared in Example 1 and Comparative Example 5 into a size of 5 cm × 5 cm. The samples were immersed in a 1 M aqueous solution of NaOH and a 0.5 M aqueous solution of H2SO4, respectively, and then the sheet resistance (Ω·cm) was adjusted to the same value as described in (1). 2 ) The sheet resistance at each immersion time (days) was obtained using the same method. The results are shown in Tables 2 and 3.
[0148]
Table 1
[0149] Referring to Table 1, the porous polymer support of the anion exchange membrane prepared in Examples 1 to 3 is a polypropylene membrane, whose porosity is 48% to 55% and whose thickness is 60 μm to 110 μm. The porous polymer support of the anion exchange membrane prepared in Comparative Example 1 is a polypropylene membrane, whose porosity is 28% and whose thickness is 120 μm. Compared with the anion exchange membrane prepared in Comparative Example 1, the sheet resistance of the anion exchange membrane prepared in Examples 1 to 3 is reduced to equal to or less than 9.6 Ω·cm 2 , and the ion exchange capacity (IEC) is increased to equal to or greater than 1.8 meq / g.
[0150] In addition, the porous polymer support of the anion exchange membrane prepared in Comparative Example 2 is a cellulose acetate nonwoven fabric support having a thickness of 60 μm and a porosity of 75%. Using a 15 wt % NaCl aqueous solution as raw water, the anion exchange membrane prepared in Comparative Example 2 was applied to an electrodialysis system for concentration, but concentration was not possible.
[0151] The porous polymer support of the anion exchange membrane prepared in Comparative Example 3 is a polyethylene / polypropylene porous polymer support having a thickness of 20 μm and a porosity of 84%. Using a 15 wt % NaCl aqueous solution as raw water, the anion exchange membrane prepared in Comparative Example 3 was applied to an electrodialysis system for concentration, but concentration was not possible.
[0152] The porous polymer support of the anion exchange membrane prepared in Comparative Example 4 is a polyethylene / polypropylene porous polymer support with a thickness of 8 μm and a porosity of 44%. The thickness of the anion exchange membrane prepared in Comparative Example 4 is too thin, resulting in the inability to fasten the module.
[0153]
Table 2
[0154]
Table 3
[0155] Table 2 shows the results of immersing the anion exchange membrane prepared in Example 1 in a 1M NaOH aqueous solution and a 0.5M H2SO4 aqueous solution, and measuring the sheet resistance according to the immersion time. Table 3 shows the results of immersing the anion exchange membrane prepared in Comparative Example 5 in a 1M NaOH aqueous solution and a 0.5M H2SO4 aqueous solution, and measuring the sheet resistance according to the immersion time. Referring to Table 2, the anion exchange membrane prepared in Example 1 was immersed in a 1M NaOH aqueous solution and a 0.5M H2SO4 aqueous solution, and measuring the sheet resistance according to the immersion time. 1M aqueous solution and H2SO4 0.5M aqueous solution, and the sheet resistance changes after 40 days were about 6.7% and 3%, respectively. Referring to Table 3, the anion exchange membrane prepared in Comparative Example 5 was immersed in NaOH 1M aqueous solution and H2SO4 0.5M aqueous solution, and the sheet resistance changes after 40 days were about 41% and 11%, respectively.
[0156] Compared with the anion exchange membrane prepared in Comparative Example 5, the anion exchange membrane prepared in Example 1 was immersed in a 1M NaOH aqueous solution and a 0.5M H2SO4 aqueous solution, respectively, and the change in sheet resistance after 40 days was small, thereby confirming its excellent chemical resistance.
[0158] It can be seen that the anion exchange membranes prepared in Examples 1 to 3 are suitable for electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, Or water electrolysis system (water electrolysis).
Claims
1. An anion exchange membrane comprising: A porous polymer support made of a membrane structure; and Anion exchange polymer, wherein The anion exchange polymer is located on the surface and inside the pores of the porous polymer support. The anion exchange groups of the anion exchange polymer are evenly distributed on the surface and inside the pores of the porous polymer support. And the anion exchange polymer is a cross-linked combination product of a composition comprising a cross-linking monomer represented by the following Chemical Formula 1: [Chemical formula 1] In the formula, X - F - , Cl - Br - or I - .
2. The anion exchange membrane according to claim 1, wherein The membrane structure is a structure with regularly arranged pores or a three-dimensional network structure.
3. The anion exchange membrane according to claim 1, wherein The porosity of the membrane structure is 30% to 80%.
4. The anion exchange membrane according to claim 1, wherein The membrane structure comprises one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone.
5. The anion exchange membrane according to claim 1, wherein The thickness of the porous polymer support is 10 μm to 110 μm.
6. The anion exchange membrane according to claim 1, wherein The anion exchange membrane has an average thickness of 10 μm to 200 μm.
7. The anion exchange membrane according to claim 1, wherein The anion exchange membrane has an ion exchange capacity equal to or greater than 1.5 meq / g.
8. The anion exchange membrane according to claim 1, wherein The sheet resistance of the anion exchange membrane is equal to or less than 10Ω·cm 2 .
9. The anion exchange membrane according to claim 1, wherein The anion exchange membrane is used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization or water electrolysis system.
10. A method for preparing an anion exchange membrane comprises the following steps: Providing a porous polymer support made of a membrane structure; preparing a composition for forming an anion exchange polymer, wherein the composition for forming an anion exchange polymer comprises a crosslinking monomer represented by the following Chemical Formula 1, a photoinitiator, and a solvent; impregnating the porous polymer support with the anion exchange polymer-forming composition to fill the surface and pores of the porous polymer support with the composition; Pressing a polyester base film on at least one surface of a porous polymer support filled with the composition to prepare a laminate having the polyester base film and the porous polymer support laminated thereon; irradiating the laminate with light and causing the composition to undergo a cross-linking reaction to form an anion exchange polymer as a cross-linked product of the composition on the surface of the porous polymer support and inside the pores; and The polyester base film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane: [Chemical formula 1] In the formula, X - F - , Cl - Br - or I - .
11. The method for preparing an anion exchange membrane according to claim 10, wherein: The crosslinking monomer represented by the Chemical Formula 1 may be included in an amount of 30 to 70 wt % based on 100 wt % in total of the anion exchange polymer-forming composition.
12. The method for preparing an anion exchange membrane according to claim 10, wherein: The porosity of the membrane structure is 30% to 80%.
13. The method for preparing an anion exchange membrane according to claim 10, wherein: The membrane structure comprises one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylether sulfide, polyetheretherketone, polyethersulfone, polysulfone, polystyrene, polyarylethersulfone and polyetherketone.
14. The method for preparing an anion exchange membrane according to claim 10, wherein: The thickness of the porous polymer support is 10 μm to 110 μm.
15. The method for preparing an anion exchange membrane according to claim 10, wherein: Before impregnating the porous polymer support with the anion exchange polymer-forming composition, the method further includes immersing the porous polymer support in a surfactant solution and drying the solution to prepare a porous polymer support having a hydrophilized surface.
16. The method for preparing an anion exchange membrane according to claim 10, wherein: The light irradiation uses UVC as ultraviolet light at 2000 mJ / cm 2 Up to 10000mJ / cm 2 irradiate with the amount of light.